Evaluation of nutritional Parameters and carotenoid pigment from Penaeus monodon of Zoea – PL 20 stages fed with live algal diet and Artemia enriched algal diet - Ramasamy, Madhumathi Mani*; Rengasamy (Recent Research in Science and Technology, 2011)
This study was subjected to investigate the nutritional value and carotenoid content of Penaeus monodon from Zoea – Post larval 20 stages when fed with five different microalgae and Artemia sp. nauplii enriched with five different microalgae. Among the algae alone treatments, P. monodon fed to Chaetoceros calcitrans showed better growth and length at Z3- M3/PL1 stages. Whereas from PL 1 – PL 20 stages of P. monodon fed with Artemia sp. naupli enriched with D. salina showed better results on the tested parameters when compared to Artemia sp. nauplii enriched with other algal sources. The maximum accumulation of carotenoids and good colouration were observed in the PL 20 stages of the animal fed with Artemia sp. nauplii enriched with Dunaliella salina. The Polyunsaturated fatty acids (PUFA) content seems to be high in P. monodon at Z3- M3/PL 1 stage when fed with C. calcitrans, whereas at PL 20 stages profile is high when fed with Artemia sp. nauplii enriched with D. salina. This study showed that besides diatoms, D. salina has the potential betacarotene pigment and supports better growth and nutritional components.